Design of Potassium‐Selective Mixed Ion/Electron Conducting Polymers. Issue 12 (5th May 2020) - Villarroel Marquez, Ariana; Salinas, Gerardo; Abarkan, Myriam; Idir, Maël; Brochon, Cyril; Hadziioannou, Georges; Raoux, Matthieu; Kuhn, Alexander; Lang, Jochen; Cloutet, Eric
Abstract: An approach providing cation‐selective poly‐(3, 4‐ethylenedioxythiophene)(PEDOT):polyelectrolyte‐mixed conductors is presented in this communication based on the structural modification of this ambivalent (ionic and electronic conductive) polymer complex. First, an 18‐crown‐6 moiety is integrated into the styrene sulfonate monomer structure as a specific metal cation scavenger particularly targeting K + versus Na + detection. This newly functionalized monomer is characterized by 1 H NMR titration to evaluate the ion selectivity. Aqueous PEDOT dispersion inks containing the polymeric ion‐selective moieties are designed and their electrical and electrochemical properties analyzed. These biocompatible inks are the first proof‐of‐concept step towards ion selectivity in view of their interfacing with biological cells and microorgans of interest in the field of biosensors and physiology. Abstract : Differentiating and sensing K + cations versus Na + through specific functionalization of mixed conducting poly‐(3, 4‐ethylenedioxythiophene) complexes.